Analisis Pengaruh Profitabilitas, Ukuran Perusahaan, dan Leverage terhadap Nilai Perusahaan Subsektor Tekstil dan Garmen - Fatihah, Dila Rizki; Tantra, Arda Raditya (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2026)
Firm value is an important indicator in assessing corporate performance and sustainability, particularly in the textile and garment industry, which faces dynamic competition and economic pressures. This study aims to analyze the effect of profitability, firm size, and leverage on firm value in textile and garment subsector companies listed on the Bursa Efek Indonesia during the 2021–2024 period. The research employed a quantitative approach using multiple linear regression analysis with SPSS version 29. The population consisted of all textile and garment subsector companies listed on the exchange. Using purposive sampling, 15 companies were selected as the sample. After eliminating outliers, a total of 42 observations were analyzed. The results indicate that profitability, measured by Return on Assets (ROA), has a positive and significant effect on firm value. Firm size, proxied by the natural logarithm of total assets, has a negative and significant effect on firm value. Meanwhile, leverage, measured by the Debt to Equity Ratio (DER), has a positive and significant effect on firm value. Simultaneously, profitability, firm size, and leverage significantly affect firm value in the textile and garment subsector. This study is expected to contribute to the literature on the determinants of firm value and serve as a reference for investors and management in formulating strategies to improve corporate performance and optimize financial structure management.